Performance of fourier-based and wavelet-based OFDM for DVB-T systems - Abdullah, Khaizuran; M. Hussain, Zahir (2007)
We present a comparative study on Fourier-based OFDM (FFT-OFDM) and wavelet-based OFDM (DWT-OFDM)in DVB-T system (DWT being the discrete wavelet transform). We found that the DWT-OFDM outperforms FFT-OFDM in AWGN and Rayleigh fading channels. For AWGN channel, the gain in term of energy per bit to noise ratio Eb/No was improved by about 5 dB when the system used Haar wavelet compared to FFT-OFDM with a cyclic prefix (CP) of 1/4-th the total OFDM symbol period, for the same BER of 0.001. Other members of Daubechies families such as db8, db16 and db32 also outperformed by the gains of 7 dB, 10 dB and 11 dB, respectively, at the same BER. We also considered Daubechies wavelet db32 and FFT-OFDM with a CP of 1/4-th the total OFDM symbol period in the presence of narrowband interference. In terms of Eb/No, DWT-OFDM surpassed FFT-OFDM by 9 dB at 0.02 BER. It is also shown that the DWT-OFDM of Daubechies db8 and db1 outperform FFT-OFDM in Rayleigh fading, both in multipath flat fading and multipath frequency selective fading. The DWT-OFDM’s with db8 and Haar outperformed FFT-OFDM by 7 and 2 dB, respectively, at BER of 0.01 in the flat fading channel. In addition, DWT-OFDM and FFT-OFDM showed about the same performance below 10 dB of Eb/No in frequency selective fading. However, the wavelet-based OFDM showed significant improvement of performance at higher than 10 dB of Eb/No.